2013
DOI: 10.32607/20758251-2013-5-3-92-98
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Parameters and Cytotoxic Activity of Recombinant Methionine γ-Lyase from Clostridium tetani, Clostridium sporogenes, Porphyromonas gingivalis and Citrobacter freundii

Abstract: The steady-state kinetic parameters of pyridoxal 5’-phosphate-dependent recombinant methionine γ -lyase from three pathogenic bacteria, Clostridium tetani, Clostridium sporogenes, and Porphyromonas gingivalis, were determined in β- and γ-elimination reactions. The enzyme from C. sporogenes is characterized by the highest catalytic efficiency in the γ-elimination reaction of L-methionine. It was demonstrated that the enzyme from these three sources exists as a tetramer. The N-terminal poly-histidine fragment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…MGL is considered to be an attractive target in pathogens for rational drug development because the enzyme is absent in mammalian hosts. Moreover, MGL is effective in cancer-cell treatment (Tan et al, 2010;Morozova et al, 2013). To date, two suicide substrates of MGL have been considered as possible new pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…MGL is considered to be an attractive target in pathogens for rational drug development because the enzyme is absent in mammalian hosts. Moreover, MGL is effective in cancer-cell treatment (Tan et al, 2010;Morozova et al, 2013). To date, two suicide substrates of MGL have been considered as possible new pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously [ 25 ], we showed that cleavage of His-tag from C. sporogenes MGL by thrombin leads to a 1.5- fold increase in the activity of the enzyme in the physiological reaction with L-methionine. In this work, we have determined the parameters of steady-state kinetics of C. sporogenes MGL without His-tag in the γ-elimination reactions of five substrates (L-methionine, L-methionine sulfoxide, S-ethyl-L-homocysteine, S-ethyl-L-homocysteine sulfoxide and O -acetyl-L-homoserine) and in the β-elimination reactions of four substrates (S-ethyl-L-cysteine, S-ethyl-L-cysteine sulfoxide, O -acetyl-L-serine and alliin).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we cloned the C. sporogenes gene ( meg L) encoding MGL with a polyhistidine fragment (His-tag) at the N-terminus of the polypeptide chain and determined some kinetic characteristics of the recombinant enzyme (His-tag MGL). C. sporogenes MGL catalyzed the γ-elimination reaction of L-methionine at a faster rate than the enzyme from C. freundii [ 24 ] and showed higher cytotoxic activity against a number of tumor cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…3.1. Overall structure C. sporogenes MGL is a homotetramer with a total molecular weight of about 170 kDa (Morozova et al, 2013). Structures of the enzyme from P. putida (Motoshima et al, 2000) and C. freundii (Mamaeva et al, 2005) identify that it belongs to the cystathionine -lyase structural subclass (Kä ck et al, 1999).…”
Section: Resultsmentioning
confidence: 99%